Factores de riesgo de anemia en las mujeres de postparto atendidas en el servicio de ginecología del hospital provincial Julius Doepfner de Zamora Chinchipe. año 2015 - Chacha Chacha, Tania Karina (2016)
This research work was to determine the risk factors for anemia in postpartum women. The research design was cross-sectional, observational, descriptive, bibliographic and field. For information survey techniques and direct observation, with their instruments the questionnaire and the observation guide 50 postpartum women who formed the sample was applied. The results indicated the situational diagnosis of postpartum anemia among data found in terms of age was 15 to 20 years with 40% incomplete secondary education with 26%, referring to ethnicity mixed with 78% rural residence with 58%, type of mild anemia with 62%. Regarding the causes found was: 76% suffered from anemia during pregnancy, 60% the rate of vaginal delivery, 66% were primiparous, regarding prenatal care from 4 to 9 to 52%, consumption micronutrients with 38% not continue consuming, concerning the type of food they consume 56% is not healthy feed and finally with 64% finding the average economic sentiment. Complications that occur during delivery were obstetric hemorrhage with 40%. Training, home visits to pregnant and postpartum women visits, open house with topics related prevention, control and postpartum care: As nursing intervention plan based on educational activities performed. Concluding that the risk factors of anemia were the lack of prenatal checkups with 48%, lack of nutritious food source of iron during pregnancy with 56%. Keywords: Anemia, Risk factors, Postpartum, Gynecology service.